A Regulatory Circuitry Between Gria2, miR-409, and miR-495 Is Affected by ALS FUS Mutation in ESC-Derived Motor Neurons - Capauto, Davide (Mol Neurobiol, 2018)
Mutations in fused in sarcoma (FUS) cause amyotrophic lateral sclerosis (ALS). FUS is a multifunctional protein involved in the biogenesis and activity of several types of RNAs, and its role in the pathogenesis of ALS may involve both direct effects of disease-associated mutations through gain- and loss-of-function mechanisms and indirect effects due to the cross talk between different classes of FUS-dependent RNAs. To explore how FUS mutations impinge on motor neuron-specific RNA-based circuitries, we performed transcriptome profiling of small and long RNAs of motor neurons (MNs) derived from mouse embryonic stem cells carrying a FUS-P517L knock-in mutation, which is equivalent to human FUS-P525L, associated with a severe and juvenile-onset form of ALS. Combining ontological, predictive and molecular analyses, we found an inverse correlation between several classes of deregulated miRNAs and their corresponding mRNA targets in both homozygous and heterozygous P517L MNs. We validated a circuitry in which the upregulation of miR-409-3p and miR-495-3p, belonging to a brain-specific miRNA subcluster implicated in several neurodevelopmental disorders, produced the downregulation of Gria2, a subunit of the glutamate α‐amino‐3‐hydroxy‐5‐methyl-4-isoxazole propionic acid (AMPA) receptor with a significant role in excitatory neurotransmission. Moreover, we found that FUS was involved in mediating such miRNA repression. Gria2 alteration has been proposed to be implicated in MN degeneration, through disturbance of Ca(2+) homeostasis, which triggers a cascade of damaging “excitotoxic” events. The molecular cross talk identified highlights a role for FUS in excitotoxicity and in miRNA-dependent regulation of Gria2. This circuitry also proved to be deregulated in heterozygosity, which matches the human condition perfectly. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s12035-018-0884-4) contains supplementary material, which is available to authorized users.